2007
DOI: 10.1021/la7012304
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Interparticle Spacing of Au−Salt Loaded Micelles and Au Nanoparticles on Flat Surfaces

Abstract: The self-organization of diblock copolymers into micellar structures in an appropriate solvent allows the deposition of well ordered arrays of pure metal and alloy nanoparticles on flat surfaces with narrow distributions in particle size and interparticle spacing. Here we investigated the influence of the materials (substrate and polymer) and deposition parameters (temperature and emersion velocity) on the deposition of metal salt loaded micelles by dip-coating from solution and on the order and inter-particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 51 publications
4
37
0
Order By: Relevance
“…This micellar approach allows control of both, the interparticle distance and the particle size. While the former is primarily determined by the length of each polymer block with additional influence of the substrate velocity during the dip coating process [20], the latter is related to the loading ratio L Au , i.e., the ratio of ligated Au within the micellar core to the total number of pyridine moieties. An example of an array of Au nanoparticles obtained in the described way is presented in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…This micellar approach allows control of both, the interparticle distance and the particle size. While the former is primarily determined by the length of each polymer block with additional influence of the substrate velocity during the dip coating process [20], the latter is related to the loading ratio L Au , i.e., the ratio of ligated Au within the micellar core to the total number of pyridine moieties. An example of an array of Au nanoparticles obtained in the described way is presented in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Details regarding the degree of order are published elsewhere. [35] Since AFM can only give reliable information on the height of the nanoparticles, we have additionally analyzed the particles by means of HR-TEM in a new series of experiments.…”
Section: Au Nanoparticles Produced By the Micelle-based Technique On mentioning
confidence: 99%
“…Also, Bansmann Electronic supplementary material The online version of this article (doi:10.1007/s00396-015-3706-5) contains supplementary material, which is available to authorized users. et al reported the formation of the Au NCP monolayers with a short-range ordered structure by dipping the Au-salt-loaded micelles on a substrate, where the particle-particle distance can be controlled in the range of several tens of nanometers by changing the dip-coating velocity [21].…”
Section: Introductionmentioning
confidence: 99%